Criminology - Adler, Freda (McGraw-Hill, 1997)
The book has four parts. Part I presents an overview of criminology. Part II includes explanations of crime and criminal behavior on the basis of the various theories developed in the twentieth century. Part III covers the various types of crimes from a legal and sociological perspestives. Part IV includes an explanation of the component parts and the functioning of the system